1999
DOI: 10.1177/004051759906900107
|View full text |Cite
|
Sign up to set email alerts
|

Surface Resistivity Behavior of Plasma Treated and Plasma Grafted Cotton and Polyester Fabrics

Abstract: Cotton and polyester fabrics are treated with radio-frequency plasma (in air) at different power levels and time intervals, and moisture content and surface resistivity behavior are investigated. Plasma treatment lowers the moisture content of cotton and enhances that of polyester. The surface resistivity of plasma treated cotton is affected by both power level and treatment time, and the surface resistivity of polyester is dramatically reduced after plasma treatment. The two fabrics are subjected to further p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 4 publications
0
27
0
Order By: Relevance
“…Although there is an abundance of literature on the surface wettability of plasma treated materials [6][7][8][9][10][11], it is still not fully described from a theoretical point of view. The aim of the present study is to look further into the effect of plasma treatment on the surface energy and wettability of polyacrylonitrile fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is an abundance of literature on the surface wettability of plasma treated materials [6][7][8][9][10][11], it is still not fully described from a theoretical point of view. The aim of the present study is to look further into the effect of plasma treatment on the surface energy and wettability of polyacrylonitrile fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly in situ polymerization is also carried out, in which fabric is treated with gaseous plasma followed by plasma polymerization of monomer vapour onto the fabric surface in the plasma reactor. Bhat and Benjamin have successfully grafted acrylamide onto cotton and polyester fabrics using RF plasma (Bhat and Benjamin, 1999). They have observed that the crease recovery angle increases and tensile strength decreases slightly.…”
Section: Radiation Induced Surface Graftingmentioning
confidence: 99%
“…In previous studies [2,3], plasma treatment has been found to be an effective way for improving color yield, levelness, and crocking fastness of pigment dyed fabrics. During plasma treatment, the fiber surface can be modified physically [4][5][6] and chemically [7][8][9]. In physical modification, active plasma species bombarding the fiber surface causes ejection of atoms on the fiber surface [10][11][12].…”
Section: Introductionmentioning
confidence: 99%